FINANCIAL MANAGEMENT STRATEGY OF REGIONAL PUBLIC SERVICE AGENCIES (BLUD) IN IMPROVING HEALTHCARE SERVICE QUALITY AT SUNGAILIAT PUBLIC HEALTH CENTER AND SINAR BARU PUBLIC HEALTH CENTER, BANGKA REGENCY - Netta Shofa; Nizwan Zukhri; Ari Agung Nugroho (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2026)
The implementation of the Regional Public Service Agency Financial Management Pattern (PPK-BLUD) provides financial flexibility for public health centers (puskesmas) to enhance service quality. Disparities in resource capacity, the number of National Health Insurance (JKN) participants, and fiscal capacity trigger differences in fund management strategies. This qualitative study aims to analyze the implementation, internal-external factors, and BLUD fund management strategies at Sungailiat Health Center and Sinar Baru Health Center in Bangka Regency. Data were collected through in-depth interviews, observations, and documentation, then analyzed using Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), Internal-External (IE) Matrix, SWOT Matrix, and Quantitative Strategic Planning Matrix (QSPM). Results indicate that fund management adheres to flexibility, effectiveness, efficiency, accountability, and transparency principles. Sungailiat Health Center achieved an IFAS score of 3.05 and EFAS score of 3.15 (Cell I IE: Grow and Build, Quadrant I SWOT). Its QSPM priority is the Strengths–Opportunities (SO) strategy (TAS 6.47), focusing on digitalization, human resource competency enhancement, and service innovation. Conversely, Sinar Baru Health Center obtained an IFAS score of 2.45 and EFAS score of 2.87 (Cell V IE: Hold and Maintain, Quadrant IV SWOT). Its priority is the Strengths–Threats (ST) strategy (TAS 5.94), emphasizing financial efficiency, budget prioritization, and medical logistics optimization. The study concludes that BLUD strategies must be contextually tailored to the specific operational conditions of each health center